2017
DOI: 10.1063/1.5000066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of location of excitation on the spiral vortices in the transitional region of a rotating-disk flow

Abstract: The laminar-turbulent transition of a rotating-disk flow dominated by global instability is studied by solving the full Navier-Stokes equations in direct numerical simulations. A flow field in the 2π/32 region is computed using a periodic boundary condition. The flow field is disturbed in two ways. In the first case, a disturbance is introduced at the Reynolds number, Re≈ 600, while in the second case, a disturbance is introduced at Re≈ 650. In both cases, wall-normal short-duration suction and blowing are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Since absolute instability and transition to turbulence occur within the same band of Reynolds numbers, Lingwood (1996) suggested that the absolutely unstable mechanism is the primary cause for the breakdown of the laminar flow. Several recent investigations on a rotating disc of finite radius suggest that absolute instability can establish globally unstable behaviour if disc edge effects are accounted for (Healey 2010;Imayama et al 2013;Pier 2013;Appelquist et al 2015Appelquist et al , 2016Lee et al 2017Lee et al , 2018. Additionally, Pier (2003) suggests that a secondary absolute instability develops near the primary absolute instability, providing an alternative route to turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Since absolute instability and transition to turbulence occur within the same band of Reynolds numbers, Lingwood (1996) suggested that the absolutely unstable mechanism is the primary cause for the breakdown of the laminar flow. Several recent investigations on a rotating disc of finite radius suggest that absolute instability can establish globally unstable behaviour if disc edge effects are accounted for (Healey 2010;Imayama et al 2013;Pier 2013;Appelquist et al 2015Appelquist et al , 2016Lee et al 2017Lee et al , 2018. Additionally, Pier (2003) suggests that a secondary absolute instability develops near the primary absolute instability, providing an alternative route to turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The flow structures on the flat surface of an infinite rotating disk in a still fluid are often explained in terms of flow instabilities (Lingwood 1995;Itoh 1996;Lee et al 2017). The surrounding fluid is sucked toward the disk surface and driven outward by centrifugal force.…”
Section: Introductionmentioning
confidence: 99%